FINANCIAL STABILITY OF AN ECONOMIC ENTITY AS A RESULT OF ADAPTATION TO THE CONDITIONS OF A VOLATILE MARKET ENVIRONMENT - Tatyana A. Chilimova (Наука Красноярья)
The analysis of the current state of the Russian economy has shown the increased role of business adaptation to external threats and risks in order to achieve financial stability. Due to its relevance, the problems of financial stability of an business entity are in the focus of attention of both foreign and domestic researchers. In the scientific literature, there are several conceptual points of view on the content of the concept of "financial stability". The presented author's understanding of financial stability is based on the relationship between risks, financial stability and financial stability. The main indicators used to assess the financial condition of an economic entity that meets or does not meet the signs of stability have been identified. The conclusions about the need to calculate individual norms of evaluation indicators reflecting the peculiarities of the functioning of each business entity are formulated in the conclusion.